2016
DOI: 10.3382/ps/pew062
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of chicken astrovirus associated with chicks that have an unusual condition known as “white chicks” in Brazil

Abstract: Chicken astrovirus (CAstV) is one of many viruses related to enteric diseases in poultry that are associated with Runting-Stunting Syndrome (RSS), which affects young chickens. CAstV was also recently associated with an unusual condition in chicks called "white chicks." Some hatcheries in certain states of Brazil have reported several incubation problems, mortality, and the presence of chicks with white plumages over the past several months. These chicks were termed locally as "white chicks." The present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 52 publications
3
31
0
1
Order By: Relevance
“…The poultry viral diseases have great economic impact on poultry industries worldwide as it leads to high mortality. Chicken astrovirus causes severe disease especially in young chickens (Bulbule et al 2013;Li et al 2013;Nunez et al 2016;Schultz-Cherry et al 2001;Smyth et al 2013;Todd et al 2009). Though culturing methods has been described for astroviruses (Baxendale and Mebatsion 2004;Nunez et al 2015), the isolation of virus is somewhat difficult due to its poor growth in the culture (Smyth et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poultry viral diseases have great economic impact on poultry industries worldwide as it leads to high mortality. Chicken astrovirus causes severe disease especially in young chickens (Bulbule et al 2013;Li et al 2013;Nunez et al 2016;Schultz-Cherry et al 2001;Smyth et al 2013;Todd et al 2009). Though culturing methods has been described for astroviruses (Baxendale and Mebatsion 2004;Nunez et al 2015), the isolation of virus is somewhat difficult due to its poor growth in the culture (Smyth et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Later on it was also found to be associated with gout (Bulbule et al 2013) and hatchability problem (Smyth et al 2013) in broiler chickens. Recently CAstV has been linked with 'white chicks', a disease characterized by weakness and white plumage of hatched chicks (Smyth et al 2013) and leading to increased mortality in chicks and embryo has also been reported in Poland and Brazil (Nunez et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This disorder (also known as malabsorption syndrome and as runting-stunting syndrome or RSS) is a multifactorial disease of chickens which results in gastrointestinal alterations along with elevated feed conversion and decreased body weight (Rebel et al 2006, Saif 2013, Nuñez et al 2016a, Nuñez et al 2016b). Bacterial, protozoal and viral agents are known to be involved in the development of outbreaks, which are also related to flock management and to the immunological status of flocks , Moura-Alvarez et al 2013, Moura-Alvarez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An additional astrovirus genotype has also been identified as a cause of encephalitis in sheep (48). Porcine astroviruses are associated with a congenital tremor syndrome in newborn piglets, while the "white chicks" hatchery disease is caused by a chicken astrovirus that also has been detected in brain tissue (49,50). Together, these examples demonstrate a previously unrecognized neurotropism of multiple astroviruses.…”
mentioning
confidence: 97%